Medire: Medication reminder mobile application with Optical Character Recognition (OCR) / Adam Syahir Azmi, Muhammad Hamiz Mohd Radzi and Mohammad Bakri Che Haron - Azmi, Adam Syahir; Mohd Radzi, Muhammad Hamiz; Che Haron, Mohammad Bakri (2022)
Medicine is the science of healing, which includes diagnosis, treatment, and the promotion of health. In addition to treating and preventing various diseases, it also refers to substances derived from plants, medications, and therapies. The correct medication can vastly improve a patient's quality of life by reducing or eliminating symptoms. However, there are issues with people's medication intake. According to a preliminary study and a survey, people are so busy dealing with their daily lives that they forget important details, including their medication intake. Aside from that, they struggle to read the information on medications. This project aims to develop Medire: Medication Reminder Mobile Application with Optical Character Recognition (OCR) to address the issue. The Mobile Application Development Life Cycle methodology is used for this project. The modified methodology consists of four phases: identification, design, development, and prototyping. In the identification and design phases, all requirements to develop the mobile application were gathered. While in the development phase, the application included Pill Reminder, Medication Cabinet, and Health Care. Pill Reminder helps users track, plan, and be reminded to take their medications on time, while Medication Cabinet uses OCR and a search function to identify each medicine's purpose. The Health Care module locates pharmacies and clinics within 10 km. Finally, all of the modules were integrated to form a prototype. In conclusion, the purpose and objectives of this project have been accomplished. It is hoped that users will benefit from using this application in the future.